Electrophysiological Evidence for Impaired Attentional Engagement with Phonologically Acceptable Misspellings in Developmental Dyslexia - Savill, Nicola; Thierry, Guillaume (Frontiers in Psychology, 2011)
Event-related potential (ERP) studies of word recognition have provided fundamental insights into the time-course and stages of visual and auditory word form processing in reading. Here, we used ERPs to track the time-course of phonological processing in dyslexic adults and matched controls. Participants engaged in semantic judgments of visually presented high-cloze probability sentences ending either with (a) their best completion word, (b) a homophone of the best completion, (c) a pseudohomophone of the best completion, or (d) an unrelated word, to examine the interplay of phonological and orthographic processing in reading and the stage(s) of processing affected in developmental dyslexia. Early ERP peaks (N1, P2, N2) were modulated in amplitude similarly in the two groups of participants. However, dyslexic readers failed to show the P3a modulation seen in control participants for unexpected homophones and pseudohomophones (i.e., sentence completions that are acceptable phonologically but are misspelt). Furthermore, P3a amplitudes significantly correlated with reaction times in each experimental condition. Our results showed no sign of a deficit in accessing phonological representations during reading, since sentence primes yielded phonological priming effects that did not differ between participant groups in the early phases of processing. On the other hand, we report new evidence for a deficient attentional engagement with orthographically unexpected but phonologically expected words in dyslexia, irrespective of task focus on orthography or phonology. In our view, this result is consistent with deficiency in reading occurring from the point at which attention is oriented to phonological analysis, which may underlie broader difficulties in sublexical decoding.